Implantação de um programa de autocontrole em um frigorífico de abate suíno em Campo Mourão – Paraná - Silva, Ricardo Macedo da (2023)
The quality control of a product starts from the arrival of the raw material until the shipment of the finished product, to guarantee a quality product it is necessary to comply with a series of legal requirements, among them is the Self Control Program. This work aims to present a self-control program for a pork slaughterhouse located in Campo Mourão- Paraná, in order to offer a quality service to customers. The program consists of steps and procedures aimed at ensuring product safety, meat quality and animal welfare, in addition to complying with legal requirements. For this, quality analyses, temperature control, production records, among others, are carried out. The program also aims to increase the company's productivity, improve the product range and ensure customer satisfaction. In addition, the program aims to encourage environmental preservation, as well as to promote actions to prevent diseases and improve animal welfare. The Self Control Program was carried out in accordance with the norms of the Agricultural Defense Agency of Paraná – ADAPAR. This information was used for the preparation and elaboration of the existing self-control worksheets in the slaughterhouse. Based on the analysis of risks and controls, recommendations will be formulated for the implementation of an effective self-control program. It is expected that, with the implementation of this program, food and environmental safety standards at the slaughterhouse will be improved, resulting in better working conditions for employees and greater consumer satisfaction with the products produced.